The impact of climate change-induced abiotic stresses on the nutritional quality of legume seeds - Machado, Joana; Nunes da Silva, Marta; Vasconcelos, Marta W; Santos, Carla S (Journal of experimental botany, 2025)
Legumes are integral to agricultural sustainability, offering multifaceted benefits ranging from enhanced yields to companion crops and improved soil health. Despite their recognized advantages, challenges such as technological lock-ins, limited breeding resources, and adverse environmental conditions pose threats to their cultivation. In this review, the complex interaction between climate change stressors, specifically drought, high temperatures, and elevated CO2 levels, and their individual and combined impacts on the nutritional quality of legumes will be discussed. This topic has not been thoroughly reviewed across multiple legume crops despite its importance under climate change. Here, we critically examine the impacts of environmental stresses on the nutritional quality of legume seeds and explore the underlying regulatory mechanisms, encompassing protein, amino acids, minerals, carbohydrates, lipids, and bioactive compounds. Key insights indicate a general need to shift legume cultivation practices, and the necessity of field studies beyond controlled environments for results that are more readily translated to the target population of environments for legume cultivation.